SIAPIK: TRANSFORMASI DIGITAL SEBAGAI BASIS PENCATATATAN INFORMASI KEUANGAN UMKM DI IBU KOTA NUSANTARA (IKN) - Gunawan, Agung; Huda Yus'an, Nurul (Jurnal GeoEkonomi, 2024)
The aim of this research is to assess the readiness to adopt the SIAPIK application as a digital financial recording technology for MSMEs in IKN. This research method is descriptive and tends to use analysis. The research was conducted in Kab. Penajam Paser Utara and Kab. Kutai Kartanegara which covers all MSMEs in the IKN area. The number of samples used was 2,456 MSMEs. Sample collection used interviews and the SIAPIK application installation and testing method. Based on the results of Canvas Business Modeling, it is known that Fish Crackers (milkfish amplang) have great potential to develop because of the unique raw materials and the IKN area will become the center of the country's capital and tourism. Apart from that, the readiness of MSMEs in the IKN area to adopt the SIAPIK application is not yet optimal because only 3.06% of business actors use this application to record business finances. The results of installation and testing show that business actors face challenges in using the SIAPIK application, this is due to the lack of accounting knowledge and the difficulty of using the SIAPIK application.